Acute Appendicitis: How Often is Appendectomy Negative? - Sh. V. Timerbulatov; M. V. Timerbulatov; S. V. Fedorov; A. R. Gafarova; V. M. Timerbulatov; V. M. Sibaev (Креативная хирургия и онкология)
Introduction. At present, medical practice lacks a unifi ed approach to the choice of therapeutic tactics for acute catarrhal appendicitis and therefore lacks understanding of negative appendectomy.   Aim. To study the incidence of negative appendectomy in acute appendicitis. Materials and methods. The methodology involved a retrospective analysis of the results of 1590 appendectomies performed from 2003 to 2005 and a prospective non-randomized study of 1112 patientsfor the period from 2018 to 2019. During the first observation period, the examination included physical and laboratory examinations, and in the second period, Alvaro scoring, ultrasound scan, and videolaparoscopy.   Results and discussion. In the first period, catarrhal forms of appendicitis were reported in 7.82 % of cases, while in the second period — in 3.04 %. The diagnoses were confi rmed pathohistologically in all cases.   Conclusion. No cases of performing negative appendectomy were reported, based on the results of clinical, endoscopic and pathomorphological examinations. However, the ambiguous interpretation of acute catarrhal appendicitis in the national clinical practice guidelines for acute appendicitis does not allow for unambiguous conclusions from the study.